2000
DOI: 10.1359/jbmr.2000.15.5.927
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Low Calcium Dialysate on Parathyroid Hormone Secretion in Diabetic Patients on Maintenance Hemodialysis

Abstract: Diabetic patients on maintenance dialysis often are characterized by a relative parathyroid hormone (PTH) deficiency and a form of renal osteodystrophy with low bone turnover known as adynamic bone. The goal of the present study was to determine whether a reduction in the dialysate calcium concentration would increase the predialysis (basal) PTH and maximal PTH level. Thirty-three diabetic maintenance hemodialysis patients with basal PTH values less than 300 pg/ml were randomized to be dialyzed with either a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Importantly, we also found that patients with a higher baseline serum Ca level showed a greater increase in serum PTH value and PTH ratio after 1 year. These results were not unexpected, because patients with a higher pre‐dialysis serum Ca level showed a greater decline in the post‐dialysis Ca level, stimulating PTH secretion more intensely . Thus, patients with a higher baseline serum Ca level should be carefully managed to avoid SHPT progression.…”
Section: Discussionmentioning
confidence: 83%
“…Importantly, we also found that patients with a higher baseline serum Ca level showed a greater increase in serum PTH value and PTH ratio after 1 year. These results were not unexpected, because patients with a higher pre‐dialysis serum Ca level showed a greater decline in the post‐dialysis Ca level, stimulating PTH secretion more intensely . Thus, patients with a higher baseline serum Ca level should be carefully managed to avoid SHPT progression.…”
Section: Discussionmentioning
confidence: 83%
“…Apart from surgical parathyroidectomy (PTX) and calcimimetics, many factors have been associated with an increased risk for ABD: old age, low protein intake and phosphate level [8], high dialysate calcium [9], excessive use of calcium and aluminium-based phosphate binders [10], excessive use of calcitriol [11], peritoneal dialysis [12], skeletal resistance to iPTH [5], and diabetes [13]. …”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, low DCa is associated with hypocalcaemia which may lead to cardiac rhythm disturbances, typically QTc prolongation, myocardial ischemia, and stunning, and hypotension due to decreased vascular resistance and lower cardiac output. Adynamic bone disease : In the presence of adynamic bone disease the use of a low DCa, probably 2.5 mEq/L, may be appropriate as it has been shown to increase serum PTH and bone‐specific alkaline phosphatase . Concomitant restriction of noncalcium‐based phosphate binders and discontinuing or reducing the dose of active vitamin D sterols may also be warranted …”
Section: Clinical Contextmentioning
confidence: 99%